THE IMPACT OF THE DRILL METHOD ON CADET’S LEARNING OUTCOME IN THE FIREMANSHIP SUBJECT - Sutiyo, Sutiyo; Andayani, Thursina; Nugraha, Wildan; Rahayu, Wulan Widiya (Journal of Airport Engineering Technology (JAET), 2024)
Firemanship is one part of a compulsory course designed to prepare cadets to know and understand attitudes, tasks, functions, and organizations, including rescue and firefighting organizations, and it is used in the Palembang Civil Aviation Polytechnic learning process, especially in the Aviation Rescue and Fire Fighting study program. This research aimed to find out (1) whether there was a significant difference in cadets' learning outcomes by applying the drill method and (2) whether there was a significant difference in cadets' learning outcomes by those who were taught using the drill method and those who were not or not. This research used a quasi-experimental design method involving 45 Palembang Civil Aviation Polytechnic cadets as a sample chosen by purposive sampling. The test was used to collect the data, while paired sample t-tests and independent t-tests were used to analyze the data. This research result found a significant difference between the learning outcomes of cadets taught with this method and those who did not. It proved that the result implies that the calculated value of r-obtained (4.256) was higher than r-table 1.681, and the significance level was 0.000 and degrees of freedom equal to 43.